Application of the Multistate Tuberculosis Pharmacometric Model in Patients With Rifampicin‐Treated Pulmonary Tuberculosis - Svensson, RJ (CPT Pharmacometrics Syst Pharmacol, 2016)
This is the first clinical implementation of the Multistate Tuberculosis Pharmacometric (MTP) model describing fast‐, slow‐, and nonmultiplying bacterial states of Mycobacterium tuberculosis. Colony forming unit data from 19 patients treated with rifampicin were analyzed. A previously developed rifampicin population pharmacokinetic (PK) model was linked to the MTP model previously developed using in vitro data. Drug effect was implemented as exposure‐response relationships tested at several effect sites, both alone and in combination. All MTP model parameters were fixed to in vitro estimates except B(max). Drug effect was described by an on/off effect inhibiting growth of fast‐multiplying bacteria in addition to linear increase of the stimulation of the death rate of slow‐ and nonmultiplying bacteria with increasing drug exposure. Clinical trial simulations predicted well three retrospective clinical trials using the final model that confirmed the potential utility of the MTP model in antitubercular drug development.